Analisis Penjadwalan Dengan Menggunakan Kurva S Pada Proyek Pembuatan Reactor Tank 30m3 - Abdillah, Giyo Sekhan; Waluyo, Minto (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2025)
Construction project activities can be defined as an activity that takes place within a limited period of time that has been determined with the allocation of certain resources and is intended to produce products whose quality criteria have been clearly outlined. In completing a construction job, scheduling is one of the things that is very important and needs to be paid attention to. PT. PDK received various projects, one of which was making a 30m^3 reactor tank. This tank work was carried out at the PT workshop. Putra Dharma Kencana. The S curve is a curve that describes the relationship between the accumulated value of development project implementation and project implementation. The weight on the S curve is the percentage of price for each job divided by the total price. If the total weight value is less than 100% then there is an error in the calculation which will affect the S curve. Work on the reactor tank was carried out according to the target, namely for 12 weeks. The disadvantage of the S curve method is the weight calculation. The weight used is the percentage of the price for each job with the total price.